Stendhal syndrome: a clinical and historical overview - Leonardo Palacios-Sánchez; Juan Sebastián Botero-Meneses; Rocío Plazas Pachón; Laura Bibiana Pineros Hernández; Juanita del Pilar Triana-Melo; Santiago Ramírez-Rodríguez (Arquivos de Neuro-Psiquiatria)
ABSTRACT It could be argued that one of the few unifying qualities all human beings share is the ability to appreciate beauty. While the object of beauty may change from one person to another, the awe and the thrill experienced by an enthralled beholder remains the same. Sometimes, this experience can be so overwhelming it can bring someone to the edge of existence. A very rare condition, known as aesthetic syndrome and, more commonly, Stendhal syndrome, entails a clinical phenomenon in which the presence of a beautiful piece of work or architecture causes dysautonomic symptoms such as tachycardia, diaphoresis, chest pains and loss of consciousness. We present an historical and clinical review of this condition.